Synthesis and Characterization of Some New Aminoimidazoles - YAHYAZADEH, A.; HAGHI, M. (Asian Journal of Chemistry, 2010)
Some new arylimidazoles and formimidoyl-1H-imidazoles derivatives have been synthesized in good yields by reaction between formamidines and base. The anilinium chloride is believed to act as a general acid catalyst and results in a significant acceleration of the rate of reaction. All these derivatives have been characterized basis of IR and 1H and 13C NMR spectral studies.